The Effect of Ethanol Extract of Punica granatum Linn. Leaves on Lipid Profiles of Dyslipidemic Rat - Kurniati, Neng Fisheri; Garmana, Afrillia Nuryanti; Sakinah, Lia Nurul (Pharmaceutical Sciences and Research, 2021)
It has been reported that peel of Punica granatum has antidyslipidemic activity. The aim of this research was to investigate the antidyslipidemic activity of Punica granatum leaf. The dried Punica granatum leaves were extracted with 96% ethanol. Rats were divided into several groups, which were normal, positive control, simvastatin at a dose of 10 mg/kg bw as reference group, and Punica granatum extract at a dose of 100 mg/kg. Before treatment, male Wistar rats were fed with high cholesterol chow for 3 months, and then plant extract was given for 4 weeks. Blood samples were collected at week 0, 12, 14, and 16 to measure the levels of total cholesterol, high-density lipoprotein (HDL)-cholesterol, low-density lipoprotein (LDL)-cholesterol, and triglyceride. Furthermore, at the last day of extract treatment, the aorta was isolated and haematoxylin-eosin stained. Administration of ethanol leaf extract of Punica granatum at a dose of 100 mg/kg for 2 weeks significantly reduced the total cholesterol and LDL-cholesterol levels up to 27.6% and 34.79%, respectively, compared to positive control group. After 4 weeks of extract treatment, the reduction of total cholesterol and LDL-cholesterol level were up to 59.9% and 75.05%, respectively. There was no effect of extract on HDL-cholesterol and triglyceride level. Furthermore, histological study showed that ethanol extract of P. granatum reduced aortic wall thickness significantly compared to untreated group. Punica granatum leaf is potential to be developed as an antidyslipidemic drug.